2001
DOI: 10.1046/j.1537-2995.2001.41121567.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical ex vivo expansion of cord blood hematopoietic stem and progenitor cells: duration of culture; the media, serum supplements, and growth factors used; and engraftment in NOD/SCID mice

Abstract: The data supported the strategy of expansion. The optimized condition may be applicable to clinical expansion for the abrogation or reduction of posttransplant cytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…12 In this study, we expanded cryopreserved and thawed NB at a condition optimized for clinical appli- cations, using TPO, SCF, FL and G-CSF in a serum-free medium. 16 Our results demonstrated that NB was significantly expanded to produce early and committed progenitor cells of the myeloid and megakaryocytic lineages. More significantly, SRC were present in the expanded product as revealed by huCD45 + cells in the BM, spleen and PB of the recipients, although in a reduced quantity.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…12 In this study, we expanded cryopreserved and thawed NB at a condition optimized for clinical appli- cations, using TPO, SCF, FL and G-CSF in a serum-free medium. 16 Our results demonstrated that NB was significantly expanded to produce early and committed progenitor cells of the myeloid and megakaryocytic lineages. More significantly, SRC were present in the expanded product as revealed by huCD45 + cells in the BM, spleen and PB of the recipients, although in a reduced quantity.…”
Section: Discussionmentioning
confidence: 54%
“…16,17 NOD/LtSZ-scid/scid mice were purchased from The Walter and Eliza Hall Institute of Medical Research (Victoria, Australia), bred and maintained in the Laboratory Animal Services Centre at the Chinese University of Hong Kong. Animals were handled under sterile conditions and maintained in microisolator cages.…”
Section: Transplantation Of Nod/scid Micementioning
confidence: 99%
See 1 more Smart Citation
“…A number of serum-free media have been used over the last few years with different results [59][60][61][62]. For obtaining sufficient numbers of progenitor cells for transplant, FCS [63] and autologous plasma [60,61] have been used in clinical expansion protocols.…”
Section: Ex Vivo Expansion Of Hscmentioning
confidence: 99%
“…Some of these most frequently used are SCF, Flt3L, Thrombopoietin (TPO), Interleukin-3 (IL-3), and IL-6. Lam et al (2001) [7] reported that use of SCF ? Flt3L ?…”
Section: Introductionmentioning
confidence: 99%